Regional density of private dentists: Empirical evidence from Austria - Martin Gächter; Peter Schwazer; Engelbert Theurl; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2012)
We investigated the determinants of disparities in the regional density of private dentists in Austria. Specifically, we focused on the relationship between the density of private dentists and their public counterparts, thereby controlling for other possible covariates of dentist density. Methods: Dentist density was measured at the district level. We used panel data of dentist density from 121 Austrian districts over the years 2001 to 2008. We applied a Hausman-Taylor framework to cope with possible endogeneity and to control for cross-district effects in the dentist density. Results: A significant negative relationship was found between the density of private and public dentists, indicating a substitution effect between the two dentist groups. A significant positive spatial relationship also existed for private and public dentists in the neighboring regions. Dental capacities in public and private hospitals and dental laboratories run by the public health insurance system did not have a significant effect on private dentist density. Conclusions: Although a strong negative relationship existed between private and public dentists within the districts, one should not draw the conclusion that private dentists in Austria are close substitutes for public dentists. Such a conclusion would require further empirical analysis on the utilization patterns of dental services and their relationships with financing mechanisms.
Keywords: I11; I18; I23; 330; Competition in health care markets; dentist location and density; models with panel data